Lithium ion battery material, material preparation method and application
By covering the surface of the negative electrode material of lithium-ion battery, the side reaction problem of the negative electrode material under high temperature and high pressure conditions is solved, the rate performance and stability of the material are improved, and the new energy vehicle and energy storage industries are met. High requirements for battery performance.
Patent Information
- Application Number
- CN202411446309.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing lithium-ion battery anode materials are prone to side reactions under high temperature and high pressure conditions, resulting in performance attenuation and slowdown in lithium ion transmission, making it difficult to meet the high requirements of convenience and safety in new energy vehicles and energy storage industries.
By coating the surface of the niobium-based negative electrode material with high dielectric constant materials such as BaTiO3, SrTiO3, and CaCu3Ti4O12, the local electric field and material stability are enhanced, and the decomposition of the electrolyte and surface side reactions under fast charging are suppressed.
It improves the rate performance and cycle stability of the negative electrode material, enhances the lithium ion transmission speed, extends battery life and improves safety.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a lithium-ion battery material, a material preparation method and an application. Background Art
[0002] Lithium-ion secondary batteries have the advantages of high operating voltage, light weight, no memory effect, low self-discharge rate, long cycle life, and high energy density. They are currently widely used in mobile phones, computers, electric vehicles, etc. In recent years, out of consideration for environmental protection, electric vehicles have been rapidly developed under the promotion of governments and automobile manufacturers, and lithium-ion secondary batteries have become the ideal power source for the new generation of electric vehicles with their excellent performance.
[0003] At present, the positive electrode materials of lithium-ion secondary batteries can be roughly divided into layered materials (represented by LiCoO2), olivine materials (represented by LiFePO4) and spinel structure materials (represented by LiMn2O4), and the negative electrode is graphite. Although lithium batteries were successfully commercialized as early as 1991, with the continuous popularization of new energy vehicles, people have higher requirements for the convenience of batteries. How to ensure that future negative electrode materials can meet the above needs is crucial to the development of the new energy vehicle industry and the energy storage industry.
[0004] The local field strength within 10 nanometers of high dielectric constant materials is relatively large, so the lithium ion conductivity of the negative electrode materials near them will be greatly enhanced, which is beneficial to the improvement of battery charging and discharging speed and rate. At the same time, faster lithium ion transmission is conducive to improving safety and life. Summary of the invention
[0005] The purpose of the embodiments of the present invention is to provide a lithium ion battery material, a material preparation method and an application, the purpose of which is to 0.143 Nb 0.286 O (TiNb2O7) and BaTiO3, SrTiO3, CaCu3Ti4O 12 The formation of a stable negative electrode material surface and the improvement of the electrochemical performance of the material can also inhibit the decomposition of the electrolyte and the occurrence of surface side reactions under fast charging.
[0006] In order to achieve the above object, the present invention is achieved through the following technical solutions: In a first aspect, the present application provides a lithium-ion battery material, wherein the lithium-ion battery material is composed of a first material and a second material adjacent to or coated on the surface of the first material, wherein the second material is composed of a high dielectric constant material, and the chemical composition of the first material is: c Nb d O e, wherein 0<c≤1, 0<d≤1, 0<e≤1, and M is at least one of Na, K, Al, Mg, Zn, Ni, Mn, Fe, Co, Ti, Y, Sc, Ru, Cu, Mo, Ge, W, Zr, Ca, Nb, Ta, P, V, S, F, B, Si, Ba, Pb, In, Ga, Sb, Si, Bi and Sr.
[0007] The first material has any of the following molecular formulas: Ni 0.166 Nb 0.333 O (NiNb2O6), Ti 0.143 Nb 0.286 O (TiNb2O7), Ti 0.069 Nb 0.345 O(Ti2Ni 10 O 29 )、Mg 0.023 Nb 0.391 O(Mg2Nb 34 O 87 )、Zn 0.023 Nb 0.391 O(Zn2Nb 34 O 87 )、Mo 0.030 Nb 0.364 O(MoNb 12 O 33 )、Ga 0.008 Nb 0.395 O(GaNb 49 O 124 )、Zr 0.016 Nb 0.387 O(ZrNb 24 O 62 ) and Ti 0.016 Nb 0.387 O(TiNb 24 O 62 ) and their doped and coated derivatives.
[0008] The chemical formula of the second material comprises BaTiM e O3, SrTiM e O3, CaCu3Ti4M e O 12 , where 0≤e≤0.3.
[0009] More preferably, the chemical formula of the high dielectric constant material is BaTiO3, SrTiO3, CaCu3Ti4O 12The doping element may specifically be at least one of Li, Na, Al, Mg, Zn, Ni, Mn, Fe, Co, Y, Sc, Ru, Cu, Mo, Ge, Ga, W, Zr, Ca, Nb, Ta, P, B, Si, Ba, Ti, Cr, Mo, Cd, Ag, Sn, Pb, S, Br, I, F or Sr.
[0010] More preferably, the lithium-ion battery material further includes a transition layer, the transition layer is formed between the second material and the first material, and the composition and structure of the transition layer are between the second material and the first material.
[0011] In a second aspect, the present application provides a method for preparing a lithium-ion battery material, comprising: The first material and the second material or a precursor of the second material are uniformly mixed to obtain a mixture.
[0012] The mixture is sintered.
[0013] More preferably, the mixture is sintered at a temperature increasing rate of 0.5°C / min to 8°C / min and then heated to 100°C-1000°C for 1h-10h.
[0014] More preferably, the median particle size D50 of the first material is 20 nm to 20 μm, and the median particle size D50 of the second material is 2 nm to 20 μm.
[0015] In a third aspect, the present application provides a lithium-ion battery slurry, wherein the slurry contains a lithium-ion battery active material, and the lithium-ion battery material is surrounded by the lithium-ion battery active material.
[0016] In a fourth aspect, the present application provides a negative electrode plate, the negative electrode plate comprising a current collector on which a lithium-ion battery material is loaded.
[0017] More preferably, the current collector is loaded with a lithium-ion battery material prepared by the preparation method of the negative electrode active material.
[0018] In a fifth aspect, the present application provides a lithium battery, the lithium battery comprising a negative electrode plate.
[0019] Compared with the prior art, the present invention has the following advantages: by coating the surface of the niobium-based negative electrode material with a high dielectric constant material, the niobium-based negative electrode material is Ti 0.143 Nb 0.286 O (TiNb2O7), when the high dielectric constant material composition is BaTiO3, SrTiO3, CaCu3Ti4O 12When the negative electrode is charged, the rate performance can be better improved, and the surface of the negative electrode material can be further stabilized. Furthermore, the adjacent or coated material increases the local electric field on the negative electrode surface, thereby improving the electrochemical performance of the material. At the same time, the titanium contained in the high dielectric constant material also has the characteristic of diffusing into the niobium-based material body during the surface coating process, thereby inhibiting the decomposition of the electrolyte and the occurrence of surface side reactions under fast charging, and improving the stability of the material surface structure. DETAILED DESCRIPTION
[0020] The present invention is described in further detail below.
[0021] A lithium-ion battery material, further the lithium-ion battery material can be a negative electrode active material, the positive electrode active material is from the inside to the outside, wherein the lithium-ion battery material is composed of a first material and a second material adjacent to the first material or coated on the surface of the first material, wherein the second material is composed of a high dielectric constant material, and the chemical composition of the first material is: M c Nb d O e , wherein 0<c≤1, 0<d≤1, 0<e≤1, and M is at least one of Na, K, Al, Mg, Zn, Ni, Mn, Fe, Co, Ti, Y, Sc, Ru, Cu, Mo, Ge, W, Zr, Ca, Nb, Ta, P, V, S, F, B, Si, Ba, Pb, In, Ga, Sb, Si, Bi and Sr.
[0022] The first material has any of the following molecular formulas: Ni 0.166 Nb 0.333 O (NiNb2O6), Ti 0.143 Nb 0.286 O (TiNb2O7), Ti 0.069 Nb 0.345 O(Ti2Ni 10 O 29 )、Mg 0.023 Nb 0.391 O(Mg2Nb 34 O 87 )、Zn 0.023 Nb 0.391 O(Zn2Nb 34 O 87 )、Mo 0.030 Nb 0.364 O(MoNb 12 O 33 )、Ga 0.008 Nb 0.395 O(GaNb 49 O 124 )、Zr 0.016 Nb 0.387 O(ZrNb24 O 62 ) and Ti 0.016 Nb 0.387 O(TiNb 24 O 62 ) and their doped and coated derivatives.
[0023] The chemical formula of the second material comprises BaTiM e O3, SrTiM e O3, CaCu3Ti4M e O 12 , where 0≤e≤0.3, further, the chemical formula of the high dielectric constant material in which M is BaTiO3, SrTiO3, CaCu3Ti4O 12 The doping element may specifically be at least one of Li, Na, Al, Mg, Zn, Ni, Mn, Fe, Co, Y, Sc, Ru, Cu, Mo, Ge, Ga, W, Zr, Ca, Nb, Ta, P, B, Si, Ba, Ti, Cr, Mo, Cd, Ag, Sn, Pb, S, Br, I, F or Sr.
[0024] Exemplarily, the first material is: Ti 0.143 Nb 0.286 O (TiNb2O7), the second material is barium titanate.
[0025] Specifically, the second material may also be a doped material, for example, Sr-doped BaTiO3, such as BaSr 0.2 Ti 0.9 O3; Zr-doped CaCu3Ti4O 12 、CaCu3Zr 0.3 Ti 3.7 O 12 etc., at this time, for the aforementioned general formula BaTiM e O3, SrTiM e O3, CaCu3Ti4M e O 12 , M selects two elements, the sum of the values of these two elements satisfies the value range of e; for example, BaSr 0.05 Cu 0.05 Ti 0.9 In O3, M selects Sr and Cu, with values of 0.05 and 0.05 respectively. At this time, the sum of the two satisfies the value range of e 0≤e≤0.3. Similarly, this doping rule also applies when M selects three or more elements.
[0026] Furthermore, the first material may also be selected to be a coated derivative, for example: SrO coated BaTiO3, that is, a layer of SrO is coated on the surface of BaTiO3. The above coating rules are also applicable to other first materials. The specific coated derivatives may be oxides, etc.
[0027] Furthermore, niobium-based negative electrode materials are prone to side reactions during the cycle process, especially during the cycle process under high temperature and high pressure, which leads to performance degradation and slows down the interfacial lithium ion transmission. 12 Titanium-based high dielectric constants such as BaTiO3 and CaCu3Ti4O are coated on the surface of niobium-based negative electrode materials to further improve the rate performance and cycle of niobium-based negative electrode materials. 12 Titanium-based materials increase the local electric field on the surface of niobium-based negative electrode materials, thereby improving the electrochemical performance of the materials. At the same time, since part of the titanium element diffuses to the surface of the niobium-based material, the stability of the niobium-based material is further enhanced.
[0028] Specifically, when the second material is coated on the surface of the first material, the lithium-ion battery material also includes a transition layer, which is formed between the second material and the first material. The composition and structure of the transition layer are between the second material and the first material. The particle size D50 of the first material is 2nm~20um. When the second material is coated on the surface of the first material, the mass of the second material is 1%-20% of the mass of the lithium-ion battery material in terms of mass percentage. Specifically, the second material can be evenly distributed on the surface of the first material, or it can be distributed in an island shape on the surface of the first material.
[0029] Further, the median particle size D50 of the second material is 2um, 5um, 8um, 11um or 14um, and the thickness of the second material is 2nm~20um. Exemplarily, the thickness of the second material can be 100nm~15um. The thickness of the second material can also be 200nm, 600nm, 1μm, 5μm or 10μm. Exemplarily, in terms of mass percentage, the mass of the second material is 0.5%-20% of the mass of the lithium-ion battery active material.
[0030] Furthermore, by forming a transition layer between the first material and the second material, the tightness of the connection between the core and the second material can be improved, so that the second material is not easy to fall off, and the entire material is more stable.
[0031] Specifically, the median particle size of the adjacent second material is close to the median particle size of the first material. Specifically, the particle size of the first material can be 10nm~20μm, and the particle size of the first material can also be 1μm~17μm; exemplarily, the particle size of the first material is 2μm, 4μm, 6μm, 8μm or 10μm, and further, the median particle size of the adjacent second material is close to the median particle size of the first material.
[0032] A method for preparing a lithium-ion battery material, comprising: Step S1, preparing a first material, mixing raw materials for preparing the first material uniformly, and then calcining.
[0033] Step S2: preparing a second material, grinding the raw material for preparing the second material to a preset particle size.
[0034] The first material and the second material or a precursor of the second material are uniformly mixed to obtain a mixture.
[0035] Step S3, sintering the mixture, the first material obtained in step S1 and the adjacent or coated second material obtained in step S2 are mixed and sintered, and the sintering may be carried out in an inert gas or an atmosphere containing oxygen, for example, an air atmosphere.
[0036] Furthermore, the median particle size D50 of the adjacent material is close to the first material and can be 10nm~20μm; the median particle size D50 of the adjacent material can also be 10nm~20μm. Exemplarily, the median particle size D50 of the adjacent second material is 2μm, 4μm, 6μm, 8μm or 10μm.
[0037] For example, 0.3 g of BaTiO 3 was weighed, put into a mortar, and ground for 60 min to make the median particle size D50 be 10 nm to 20 μm.
[0038] Specifically, the mixture is sintered at a temperature increase rate of 0.5°C / min to 8°C / min and then heated to 100°C-1000°C for 1h-10h.
[0039] Specifically, the median particle size D50 of the first material is 20 nm to 20 μm, and the median particle size D50 of the second material is 2 nm to 20 μm.
[0040] For example, 100 g of calcium carbonate, 319.464 g of titanium dioxide and 238.635 g of copper oxide were weighed, put into a mortar, and ground for 60 min. Then, the ground powder was placed in a sintering furnace and calcined at 900 ° C for 10 h to finally obtain CaCu3Ti4O 12 Material, median particle size D50 is 10nm~20μm.
[0041] Exemplarily, the first material prepared in step S1 and the coating material prepared in step S2 are sintered in an air atmosphere, and the temperature is increased to 500° C.-1000° C. at a heating rate of 0.5° C. / min to 8° C. / min and sintered for 1 h-10 h.
[0042] Exemplarily, the first material prepared in step S1 and the coating material prepared in step S2 are sintered in an air atmosphere, and the temperature is increased to 550° C.-950° C. at a heating rate of 1° C. / min to 7.5° C. / min and sintered for 1.5 h to 9.5 h.
[0043] Exemplarily, the core material prepared in step S1 and the coating material prepared in step S2 are sintered in an air atmosphere, and the temperature is increased to 600°C, 700°C, 800°C or 900°C at a heating rate of 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min or 6°C / min, and sintered for 2h, 3h, 4h, 5h, 6h, 7h, 8h or 9h.
[0044] Exemplarily, the first material obtained in step S1 and the adjacent second material obtained in step S2 are sintered in an air atmosphere, and the temperature is increased to 200° C.-500° C. at a heating rate of 0.5° C. / min-8° C. / min and sintered for 1 h-10 h.
[0045] Exemplarily, the first material obtained in step S1 and the adjacent second material obtained in step S2 are sintered in an air atmosphere, and the temperature is increased to 250° C.-450° C. at a heating rate of 1° C. / min to 7.5° C. / min and sintered for 1.5 h to 9.5 h.
[0046] Exemplarily, the core material prepared in step S1 and the adjacent second material prepared in step S2 are sintered in an air atmosphere, and the temperature is increased to 300°C, 350°C, 400°C or 450°C at a heating rate of 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min or 6°C / min, and sintered for 2h, 3h, 4h, 5h, 6h, 7h, 8h or 9h.
[0047] A lithium ion battery slurry contains a lithium ion battery active material, and lithium ion battery materials are arranged around the lithium ion battery active material.
[0048] A negative electrode plate comprises a current collector on which lithium-ion battery materials are loaded.
[0049] Specifically, the current collector is loaded with a lithium-ion battery material prepared by the preparation method of the negative electrode active material.
[0050] Specifically, there is the negative electrode active material provided by any of the above embodiments; or the current collector is loaded with the negative electrode active material prepared by the preparation method of the negative electrode active material provided by any of the above embodiments.
[0051] A lithium battery, the lithium battery includes a negative electrode plate, specifically, the lithium battery also includes at least two of a separator, an electrolyte, a negative electrode, a lithium supplement, and a negative electrode active material provided by any of the above embodiments, further, the negative electrode contains an active material that can occlude and release lithium ions, specifically, such as graphite, Li metal, a metal that can form an alloy with Li metal, and a mixture or alloy thereof, as a metal that can form an alloy with Li (or referred to as an "alloying material"), preferably one or more of aluminum, silicon, tin, bismuth and indium.
[0052] Further, the electrolyte can be a commonly used liquid electrolyte or a solid electrolyte. Further, the liquid electrolyte can be composed of an organic solvent and a lithium salt, and the organic solvent can be selected from one or more of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, butylene carbonate, ethylene sulfite, propylene sulfite, diethyl sulfite, γ-butyrolactone, dimethyl sulfoxide, ethyl acetate, methyl acetate, tetrahydrofuran, dimethylmethane, 2-dimethyltetrahydrofuran, 1,2-dimethylethane, 1,3-dioxolane and diethylene glycol dimethyl ether.
[0053] Specifically, the liquid electrolyte may contain electrolyte additives of elements such as N, P, Si, B, F, S, or electrolyte additives containing carbonyl groups or benzene rings.
[0054] Furthermore, the solid electrolyte can be Li 3 x La 2 / 3-x TiO3 (0≤x≤2 / 3) perovskite, with the general formula Li x M y NaSICON of (PO4)3 (1≤x≤3, 1≤y≤2, M is selected from one or more of Ge, Al, Ti, Ga, Zr, Fe and Nb), ceramic oxides having a garnet structure, sulfides composed of Li2S-P2S5 and Li2S-Ge2S5, and solid electrolytes having other crystalline or amorphous structures, for example, such as Li3N, LISICON (Lithium SuperIonic Conductor), Thio-LISICON (Li 3.25 Ge 0.25 P 0.75S4), one or more of oxide-based, sulfide-based, phosphate-based and polymer-based materials such as LiPON and PEO, specifically, ceramic oxides having a garnet structure such as oxides Li5La3M2O 12 (M=Nb or Ta), Li6ALa2M2O 12 (A=Ca, Sr or Ba; M=Nb or Ta), Li 5.5 3M 1.75 B 0.25 O 12 (M=Nb or Ta; B=In or Zr), Li7La3Zr2O 12 and Li 7.06 M3Y 0.06 Zr 1.94 O 12 (M=La, Nb or Ta).
[0055] Furthermore, when a solid electrolyte is used, the particle size of the solid electrolyte particles may be 0.1 to 20 μm, preferably 0.5 to 10 μm.
[0056] Furthermore, the lithium salt can be selected from one or more of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium difluorooxalatoborate, and lithium bis(oxalatoborate).
[0057] Furthermore, the lithium supplement is a substance containing lithium, such as lithium powder, lithium strip, lithium rod, organic lithium, inorganic lithium, including but not limited to Li6CoO4, Li2NiO2, Li2S, Li5FeO4, LiF, Li2O, Li2O2, Li3N and other substances.
[0058] Embodiment 1 A conventional negative electrode active material is prepared according to the following steps: Weigh 15.38g of niobium oxide and 4.52g of titanium dioxide material, mix them evenly, and sinter them at 1200 degrees Celsius for 12 hours to obtain sample 1 titanium niobate negative electrode. Grind the barium titanate nanoparticles with a sand mill for 0.5h and 3h to obtain barium titanate materials with a median particle size of 1um and 0.1um primary particle size, respectively. Mix 0.3g of barium titanate material with a median particle size of 1um and 10g of titanium niobate negative electrode, and sinter them at 500℃ to obtain sample 2. Mix 0.3g of barium titanate material with a median particle size of 0.1um and 10g of titanium niobate negative electrode, and sinter them at 500℃ to obtain sample 3.
[0059] Embodiment 2 Weigh 1g of calcium carbonate, 3.19464g of titanium dioxide, 2.38635g of copper oxide, and 40g of sample 4Ti2Nb 10O 29 , put it into a mortar and grind it for 60 minutes, then place the ground powder in a sintering furnace and calcine it at 900℃ for 10 hours to finally obtain sample 5, CaCu3Ti4O 12 Coated Ti2Nb 10 O 29 Material.
[0060] Embodiment 3 26.6 g of niobium oxide and 9.27 g of nickel hydroxide material were uniformly mixed and sintered at 1100 degrees Celsius for 10 hours to obtain sample 6, NiNb2O6 negative electrode material.
[0061] 0.1gCaCu3Ti4O 12 Mixed with 5g of sample 6 and calcined at 600℃ for 10h, finally obtaining sample 7, CaCu3Ti4O 12 Coated NiNb2O6 material.
[0062] It should be noted that the electrochemical performance test of the negative electrode active material of the above samples was carried out.
[0063] Example 4: Preparation of negative electrode sheet The positive electrode active materials of samples 1-7 in Examples 1 to 3, carbon black as a conductive additive, and polyvinylidene fluoride (PVDF) as a binder were dispersed in N-methylpyrrolidone (NMP) at a weight ratio of 80:10:10 and mixed evenly to prepare a uniform positive electrode slurry. The uniform negative electrode slurry was evenly coated on a copper foil current collector and dried at 55°C to form a pole piece with a thickness of 100 μm. The pole piece was placed on a roller press (pressure was about 1 MPa×1.5 cm2), cut into discs with a diameter of φ14 mm, and then placed in a vacuum oven at 120°C for 6 h. After natural cooling, it was taken out and placed in a glove box for use as a positive electrode piece.
[0064] Embodiment 5: Assembling lithium-ion secondary batteries In a glove box filled with an inert atmosphere, metallic lithium is used as the negative electrode of the battery, a three-layer film of PP / PE / PP coated with aluminum oxide on both sides is placed between the positive and negative electrodes as a separator, a commonly used carbonate electrolyte is added dropwise, and the electrode prepared in step S1 is assembled into a button battery of model CR2032.
[0065] Example 6: Battery rate cycle performance test The button cell prepared in Example 5 was left at room temperature (25°C) for 10 h, and then the button cell was activated by charge and discharge. Then, a charge and discharge cycle test was performed on the button cell prepared above using a Blue Power Battery Charge and Discharge Tester. The operation was as follows: At 25°C, the discharge capacity and coulombic efficiency of the button cells assembled with the positive electrode active materials of samples 1-7 were shown in the following table after cycling at a rate of 0.1C for 1 week, 1C for 3 weeks, and 5C for 196 weeks:
[0066] Furthermore, it can be concluded from the above table that the first-cycle efficiency, capacity at 5C and capacity retention rate after 200 cycles of the niobium-based negative electrode material after high dielectric constant coating are significantly improved compared with the original material.
[0067] This specific embodiment is merely an explanation of the invention and is not a limitation of the invention. After reading this specification, those skilled in the art may make non-creative modifications to this embodiment as needed. However, as long as they are within the scope of protection of the invention, they are protected by patent law.
Claims
1. A lithium-ion battery material, wherein the lithium-ion battery material is composed of a first material and a second material adjacent to or coated on the surface of the first material, wherein the second material is composed of a high dielectric constant material, characterized in that: The chemical composition of the first material is: M c Nb d O e , wherein 0<c≤1, 0<d≤1, 0<e≤1, M is at least one of Na, K, Al, Mg, Zn, Ni, Mn, Fe, Co, Ti, Y, Sc, Ru, Cu, Mo, Ge, W, Zr, Ca, Nb, Ta, P, V, S, F, B, Si, Ba, Pb, In, Ga, Sb, Si, Bi and Sr; The first material has any of the following molecular formulas: Ni 0.166 Nb 0.333 O (NiNb2O6), Ti 0.143 Nb 0.286 O (TiNb2O7), Ti 0.069 Nb 0.345 O(Ti2Ni 10 O 29 )、Mg 0.023 Nb 0.391 O(Mg2Nb 34 O 87 )、Zn 0.023 Nb 0.391 O(Zn2Nb 34 O 87 )、Mo 0.030 Nb 0.364 O(MoNb 12 O 33 )、Ga 0.008 Nb 0.395 O(GaNb 49 O 124 )、Zr 0.016 Nb 0.387 O(ZrNb 24 O 62 ) and Ti 0.016 Nb 0.387 O(TiNb 24 O 62 ) and its doped and coated derivatives; The chemical formula of the second material comprises BaTiM e O3, SrTiM e O3, CaCu3Ti4M e O 12 , where 0≤e≤0.
3.
2. The lithium-ion battery material according to claim 1, characterized in that In the chemical formula of the high dielectric constant material, M is BaTiO3, SrTiO3, CaCu3Ti4O 12 The doping element may specifically be at least one of Li, Na, Al, Mg, Zn, Ni, Mn, Fe, Co, Y, Sc, Ru, Cu, Mo, Ge, Ga, W, Zr, Ca, Nb, Ta, P, B, Si, Ba, Ti, Cr, Mo, Cd, Ag, Sn, Pb, S, Br, I, F or Sr.
3. The lithium-ion battery material according to claim 1, characterized in that The lithium-ion battery material further includes a transition layer, which is formed between the second material and the first material, and the composition and structure of the transition layer are between the second material and the first material.
4. A method for preparing a lithium ion battery material, characterized in that: Used to prepare the positive electrode active material according to claims 1 to 3, comprising: uniformly mixing the first material and the second material or a precursor of the second material to obtain a mixture; The mixture is sintered.
5. The method for preparing lithium ion battery material according to claim 4, characterized in that: The mixture is sintered under the conditions of heating to 100°C-1000°C at a heating rate of 0.5°C / min-8°C / min and sintering for 1h-10h.
6. The method for preparing lithium ion battery material according to claim 5, characterized in that: The median particle size D50 of the first material is 20 nm to 20 μm, and the median particle size D50 of the second material is 2 nm to 20 μm.
7. A lithium ion battery slurry, characterized in that: The slurry contains the lithium ion battery active material, and the lithium ion battery material according to any one of claims 1 to 6 is disposed around the lithium ion battery active material.
8. A negative electrode plate, characterized in that: The negative electrode plate comprises a current collector, and the lithium-ion battery material according to any one of claims 1 to 3 is loaded on the current collector.
9. The negative electrode sheet according to claim 8, characterized in that: The current collector is loaded with a lithium ion battery material prepared by the method for preparing a lithium ion battery material according to any one of claims 4 to 6.
10. A lithium battery, characterized in that: The lithium battery comprises the negative electrode sheet according to any one of claims 8 to 9.
Citation Information
Patent Citations
Oceanic capacitive electrode
CN104502981A
Lithium ion battery cathode material and non-aqueous electrolyte batterie
CN109244443A
Lithium ion battery anode material and non-aqueous electrolyte battery
CN109360978A
Lithium-ion battery anode material, non-aqueous electrolyte lithium-ion battery and preparation method of non-aqueous electrolyte lithium-ion battery
CN109904441A
Titanium-based composite material with core-shell structure as well as preparation method and application of titanium-based composite material
CN114335503A
Cited By
Three-dimensional flower-shaped carbon-supported CuNb2O6 material as well as preparation method and application thereof
CN121983431A
